1971
DOI: 10.1021/i160040a015
|View full text |Cite
|
Sign up to set email alerts
|

A Shielded Hot-Wire Probe for Highly Turbulent Flows and Rapidly Reversing Flows

Abstract: A shielded hot-wire probe has been developed which permits the determination of mean velocities, rms velocities, and other turbulence parameters in highly turbulent flow fields and in rapidly reversing flows. The instantaneous velocity vector in the flow field may point in any direction. The shield is a small disk with a hole in its center. Two wires are placed close and parallel to each other inside the hole and normal to the axis of the hole. The effect of the thermal wake of the upstream wire on the downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(50 citation statements)
references
References 4 publications
0
50
0
Order By: Relevance
“…The parameters measured were the induced current density, magnetic flux and temperature difference. The velocity was then estimated approximately from the"relation 6) ρ…”
Section: Literature Surveymentioning
confidence: 99%
See 4 more Smart Citations
“…The parameters measured were the induced current density, magnetic flux and temperature difference. The velocity was then estimated approximately from the"relation 6) ρ…”
Section: Literature Surveymentioning
confidence: 99%
“…For the single channel units four different geometries were tested in a vertical model.The velocities, (calculated from the temperature measurements) showed that the most intense flow around the loop was achieved when the top half of the channel had one sharp corner of an angle, 30° < a < 60°, and the bottom half was at a circular shape (see Fig. (1)(2)(3)(4)(5)(6)…”
Section: Literature Surveymentioning
confidence: 99%
See 3 more Smart Citations